PPPU BULETIN (SPECIAL EDITION, VOLUME 2), Asasi Eco Ambassador - Maybelline Goh, Boon Ling; Norfarahin, Norwen; Mohd Aminudin, Mustapha; Mohamad Fhaizal, Mohamad Bukhori; Muhd Ridwan, Abd Rahman; Mohamad Razif, Othman (PPPU Publication, 2023)
Asasi Eco Ambassadors fosters learning in a natural environment creating an educational environment that harnesses the natural world to facilitate meaningful learning experiences. This approach recognizes the value of outdoor settings for enhancing education and offers numerous benefits for our Asasi students. We take pride in transformative learning in our biology course.